FINANCIAL INSTABILITY IN ROMANIA - Cristian, IONESCU (Strategii Manageriale, 2014)
The aim of this paper is to empirically study the concept of financial stability in Romania, from both a monetary policy perspective and a financial perspective. In this paper, I also compute an aggregate index of financial stability, for the period 2008-2013, explaining the correlations between several extremely important macroeconomic and sectorial variables and financial stability. The article also debates the aspect of policy instruments that aim to promote, highlighting the undertaken measures and also giving some measures recommendations, pointing out the main pillars: crises management; cross-sectoral challenges; banking sector; securities markets and capital markets; insurance sector; pensions sector; access to financial services.